Characterizing cortical responses to short-term multidisciplinary intensive rehabilitation treatment in patients with Parkinson’s disease: A transcranial magnetic stimulation and electroencephalography study - Pei, Guangying; Liu, Xinting; Huang, Qiwei; Shi, Zhongyan; Wang, Li; Suo, Dingjie; Funahashi, Shintaro; Wu, Jinglong; Zhang, Jian; Fang, Boyan (Frontiers in Aging Neuroscience, 2022)
Combined transcranial magnetic stimulation and electroencephalography (TMS-EEG) is a powerful noninvasive tool for qualifying the neurophysiological effects of interventions by recording TMS-induced cortical activation with high temporal resolution and generates reproducible and reliable waves of activity without participant cooperation. Cortical dysfunction contributes to the pathogenesis of the clinical symptoms of Parkinson’s disease (PD). Here, we examined changes in cortical activity in patients with PD following multidisciplinary intensive rehabilitation treatment (MIRT). Forty-eight patients with PD received 2 weeks of MIRT. The cortical response was examined following single-pulse TMS over the primary motor cortex by 64-channel EEG, and clinical symptoms were assessed before and after MIRT. TMS-evoked potentials were quantified by the global mean field power, as well as oscillatory power in theta, alpha, beta, and gamma bands, and their clinical correlations were calculated. After MIRT, motor and nonmotor symptoms improved in 22 responders, and only nonmotor function was enhanced in 26 nonresponders. Primary motor cortex stimulation reduced global mean field power amplitudes in responders but not significantly in nonresponders. Oscillations exhibited attenuated power in the theta, beta, and gamma bands in responders but only reduced gamma power in nonresponders. Associations were observed between beta oscillations and motor function and between gamma oscillations and nonmotor symptoms. Our results suggest that motor function enhancement by MIRT may be due to beta oscillatory power modulation and that alterations in cortical plasticity in the primary motor cortex contribute to PD recovery.